STRATEGI PEMERINTAH KABUPATEN KUANTAN SINGINGI DALAM MERAIH PENGHARGAAN UNIVERSAL HEALTH COVERAGE (UHC) TAHUN 2022 - Andini, Mutiara Azzaria; ', Muchid (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2024)
Universal Health Coverage (UHC) is a health assurance system that ensures all of the population or at least 95% (nine-five percent) of the total population has been registered as a participant in the National-Kartu Indonesia Health Assurance Program. (JKN). The various strategies undertaken by the Singingi district of Kuantan towards Universal Health Coverage (UHC) is a real step by the Government of Singingi County in guaranteeing public health security. The research aims to identify strategies and factors supporting the district of Kuantan Singingi in achieving the Universal Health Coverage award. (UHC). This research used the strategy theory by Hadari Nawawi: aggressive strategy, preventive strategy, and innovative strategy. The research used qualitative descriptive methods and data collection techniques based on interviews, documentation, and library studies. The results of this research show that the Government's strategy of Kuantan Singingi district in achieving the award of Universal Health Coverage (UHC) by improving access to healthcare services and protection of healthcare costs. However, there is no regulation that regulates the basis of policy making. Supporting factors for achieving the award is the fulfillment of the human resources of health, the administration of Integrated Data of Social Welfare (DTKS), the presence of leadership commitment, the fulfilment of indicators and cooperation between the health service, the social service empowerment of communities and village, the population service and civil registration, and the BPJS health. Keywords: Government Strategy, Universal Health Coverage (UHC)